2013
DOI: 10.1097/bcr.0b013e3182839aca
|View full text |Cite
|
Sign up to set email alerts
|

Donor Site Healing Dynamics

Abstract: Understanding the physiology of donor site healing will lead to advances in how these wounds are treated and may ultimately allow faster healing, more frequent autografting, and more effective care of the burn-injured patient. Unfortunately, a paucity of data exists regarding perfusion metrics over the course of donor site healing. Furthermore, there are no studies that interrelate indices of perfusion with the molecular and cellular processes of donor site healing. Male Duroc pigs were anesthetized and donor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In fact, dipeptidyl peptidase IV and aminopeptidase have been identified in burn wound exudate with a significantly different ratio from that found in plasma [164]. Other work on local wound biomarkers using biopsies has shown that a host of proteins are upregulated during wound healing [165]. More work is needed to establish a biomarker profile that can accurately predict wound healing and to identify potential novel areas for therapeutic intervention.…”
Section: Other Considerations and Future Directionsmentioning
confidence: 99%
“…In fact, dipeptidyl peptidase IV and aminopeptidase have been identified in burn wound exudate with a significantly different ratio from that found in plasma [164]. Other work on local wound biomarkers using biopsies has shown that a host of proteins are upregulated during wound healing [165]. More work is needed to establish a biomarker profile that can accurately predict wound healing and to identify potential novel areas for therapeutic intervention.…”
Section: Other Considerations and Future Directionsmentioning
confidence: 99%
“…Swine with 3 inch by 3 inch wide and 0.06 inch deep wounds were biopsied every 2 days until healing at 2 weeks, and were the source of biopsies tested for the early presence of fibrocytes until day 14. Our partial thickness wounds reliably heal within 14 days and do not typically result in raised scar 18 . These wounds are well known to our lab to produce a model of normal partial-thickness wound healing, and were interesting to us for the purpose of demonstrating fibrocytes in a model that did not ultimately exhibit hypertrophic healing.…”
Section: Discussionmentioning
confidence: 74%
“…These data indicate that the application of higher viability ASCS increased the rate of % re-epithelialization. In addition, the previously published grading scale for % re-epithelialization 19 was validated here by comparing re-epithelialization scores from blinded assessors with actual measurements of % re-epithelialization made by digital planimetry. This comparison, which showed strong agreement between the two different measurements, indicates that scoring can be used as an option in lieu of actual measurements of % re-epithelialization in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Re-epithelialization was measured using two different techniques. In the first technique, digital pictures were used to grade percent re-epithelialization based on a previously published method 19 . Two individual blinded reviewers graded digital pictures from Days 5, 7, 12, and 14 for re-epithelialization and each picture was given a score from 0 to 5.…”
Section: Re-epithelializationmentioning
confidence: 99%